Faking, Forging, Counterfeiting - Becker, Daniel (Edition Kulturwissenschaft, 2017)
Forgeries are an omnipresent part of our culture. They are closely related to historically and culturally informed ideas of authenticity, legality, authorship, creativity, tradition and innovation. Based on the concept of mimesis, the volume illustrates that forgeries are thus not to be understood as a negative copy or disgraced rip-off of an original - but as an autonomous aesthetic practice, a creative act in itself. The contributions focus on such different implementations such as faked traditions, pseudotranslations, imposters, identity theft, and hoaxes in different arts and historic contexts. Most importantly, they scrutinize the bonds and borders between original and forgery, and turn out their epistemic capability.